Assessing the Efficiency and CO2 Reduction Performance of China’s Regional Wind Power Industry Using an Epsilon-Based Measure Model - Tian, Ze; Xiao, Qin-Wen; Ren, Fang-Rong (Frontiers in Energy Research, 2021)
China has become the largest wind power installation market in the world, and on such a large scale its wind power industry contributes to the sustainability of electricity generation and reduction of carbon emissions, yet has problems such as wind curtailment, insufficient wind power consumption, and regional disparities. Thus, this research uses an epsilon-based measure (EBM) data envelopment analysis (DEA) model to evaluate and compare wind power electricity generation efficiency and CO2 emission reduction efficiency in the eastern, central, western, and northeastern regions of China for the period 2013-2017. The empirical results show that the nation’s overall wind power efficiency presents a significant upward trend, in which the western and northeastern regions have increased the most, while the east region has increased the least. Technical inefficiency is mainly due to diseconomies of scale in China’s wind power industry. Moreover, CO2 emission reduction in the four regions exhibits high efficiency, and the regions’ efficiencies are very consistent with that of installed capacity efficiency. Finally, this study’s policy implications are that industry development plans should be made according to local conditions as well as cross-regional trade of wind power electricity and that the upgrading of wind power generation capacity should be encouraged.